Effect Modification of Selenium Supplementation by Intake and Serum Concentrations of Antioxidants on the Development of Metachronous Colorectal Adenoma. (7th February 2023) - Jacobs, Elizabeth T.; Martinez, Jessica; Batai, Ken; Lance, Peter; Trejo, Mario; Saboda, Kathylynn; Cordova, Catherine; Chew, Wade; Habila, Magdiel; Chow, H.-H. Sherry
Abstract: Background: Selenium (Se) is a trace element that has been investigated as a potential chemopreventive agent for colorectal cancer. Dietary intake of other antioxidant nutrients may modify the effect of Se. Objective: We examined the association between intake and serum concentrations of retinol, β-carotene, β-cryptoxanthin, lycopene, lutein/zeaxanthin, and α- and γ-tocopherol and the development of metachronous colorectal adenoma, and if these nutrients modified the effect of Se. Methods: We conducted a prospective study of 1874 participants from the Se Trial with data for antioxidant intake, as well as a subcohort of 508 participants with serum biomarker concentrations. Results: Statistically significantly lower odds for the development of metachronous adenoma were observed for those participants in the highest tertile of intake for lutein/zeaxanthin compared to the lowest, with an OR (95% CI) of 0.72 (0.56-0.94). No effect modification for intake of any nutrient was observed. However, circulating concentrations of lycopene exhibited statistically significant effect modification of selenium supplementation ( p < 0.06), Conclusion: These findings show that intake and circulating concentrations of antioxidant nutrients were not consistently associated with reduced odds for the development of metachronous lesions, although blood concentrations of lycopene may modify the effect of selenium supplementation.